Formal and informal modalities for policing cybercrime across the Taiwan Strait. - Chang, Lennon Y.C. (Policing & Society, 2013)
Cybercrime across the Taiwan Strait has become a global issue. Due to the large number of Internet users and the special political situation across the Taiwan Strait, the Republic of China (Taiwan hereafter) and the People's Republic of China (China hereafter) are two countries where malicious computer activity is rampant. Malicious computer activity across the Taiwan Strait has an impact not only on Taiwan and China but also on many other countries. For example, it has been reported that there have been computer attacks against the USA originating from computers in Taiwan but controlled by command and control servers in China. It is important to understand the current policing measures taken by Taiwan and China against cybercrime; however, there is limited empirical research on this issue. To fill this gap, this paper will, based on interviews conducted in Taiwan and China in 2008–2009, discuss current problems and issues that the Taiwanese and Chinese governments face when policing cybercrime. It will also examine whether current existing semi-governmental and informal cooperative measures against cross-Strait crime are adequate in addressing the problem of cross-Strait cybercrime.